Peran Organisasi Santri dalam Mengembangkan Ghirah Belajar Santri di Pesantren - Nur, Kholidah; Nasution, Suryadi (Institut Agama Islam Negeri Kendari, 2022)
This study aims to describe the role of the student organization in one of the Islamic boarding schools in North Sumatera in fostering the spirit of learning. Using a phenomenological approach, the data was gathered through direct observation of students’ activities and triangulated by the interviews with research informants. The findings of this study revealed the role of the student organization in the mudzakarah activities in terms of nahwu-sharaf, which occur on a daily basis in the morning and evening. The student organization’s existence is measured through achievements in the evaluation of formal education and the dominance in scientific mutsabaqoh activities carried out by pesantren leaders on a yearly basis.Keywords: mudzakarah; nahwu-sharaf; pesantren; student organization